Bothriolepis (Placodermi, Arthrodira) from Iveragh Peninsula (Ireland) - CT-Data, 3D-Models, and Phylogenetic Analyses Files - Dupret, Vincent (Uppsala University, 2022)
The current data set refers to the study of fossil fish material from Southwest Ireland (Placodermi, Antiarchi; Givetian of the Iveragh Peninsula). The data consist of SEM elemental mapping (section 1), CTscan image stacks and subsequent working files (i.e. segmentation, visualisation files, STLs and 3D PDF files; sections 2-5), as well as phylogenetic analyses related to the genus Bothriolepis studied in the article (section 6).
* Zoobank LSID for article: urn:lsid:zoobank.org:pub:0438B3D4-AEAA-4000-A1CB-B5DA0ECA466F
* Zoobank LSID for taxon Bothriolepis dairbhrensis: urn:lsid:zoobank.org:act:B577F075-1EF6-48A5-8C7C-E64E36E2BC4E

The dataset corresponding to the article

Dupret, Byrne, Castro, Hammer, Higgs, Long, Niedźwiedzki, Qvarnström, Stössel & Ahlberg. In Press. The Bothriolepis (Placodermi, Antiarcha) material from the Valentia Slate Formation of the Iveragh Peninsula (middle Givetian, Ireland): morphology, evolutionary and systematic considerations, phylogenetic and palaeogeographic implications. PLOS ONE.
with the LSID urn:lsid:zoobank.org:pub:0438B3D4-AEAA-4000-A1CB-B5DA0ECA466F
and the species Bothriolepis dairbhrensis Dupret, Byrne, Castro, Hammer, Higgs, Long, Gzegorz Niedźwiedzki, Qvarnström, Stössel & Ahlberg
with the LSID urn:lsid:zoobank.org:act:B577F075-1EF6-48A5-8C7C-E64E36E2BC4E

is composed of the following files:

1. Elemental analysis (SEM)
equipment: Hitachi S–3600N Scanning Electron Microscope (SEM); JPGS are original output.

2. CT-scans datasets
In London, the material was CT-scanned with a Nikon HMX ST 225 system, Nikon Metrology, Leuven, Belgium, with a tungsten reflection target. Detailed settings files were adjusted for each specimen and are given in associated documentation "S2 Table-scan properties.xlsx". Two specimens required stitching performed with an in-house NHM script written in Octave. In Oslo, the scanning was carried out with a Nikon Metrology XT H 225 ST microfocus CT instrument at the Natural History Museum, University of Oslo, at 160-220 kV, 1 s exposure time, 3016 projections, and with tin filters of varying thickness. Voxel resolution was 75 µm or better. Detailed settings are given in in associated documentation "S2 Table-scan properties.xlsx".

3. Drishti and Mimics files (segmentation)

4. STL files

5. 3D pdfs
In Mimics, each individual structure corresponding to a mask was used to generate a high quality 3D object, itself transformed into an STL file. Each 3D object was duplicated and relocated in the 3D space; once again STLs were generated. The STL files were then imported into Materialise 3-matic (v. 15.0) and were reorganised into anatomical ensembles (head, fin, etc.) in both original and correct positions. Each STL surface was then simplified and corrected using the following functions: Filter Sharp Triangles with filter distance 0.01; Filter Small Edges with filter distance 0.01; Improve Mesh with shape quality high/medium, maximum geometrical error 0.07, and maximal edge length 20.0. A 3D pdf file was finally generated and open in Adobe Acrobat to take pictures used in figures of the current article.

for the following specimens
a. NMING:F35203-UU210ab_HQ
Bothriolepis dairbhrensis sp. nov. Incomplete lateral plate and fragment of indeterminate plate. Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 10 mm.
Please note that within the Mimics project files for this specimen µm is incorrectly given as a base of measurement when it should be mm (millimeters). All other processing has been performed treating the source data as being scaled in millimeters.

b. NMING:F35229-CH003
Bothriolepis dairbhrensis sp. nov. Assemblage of indeterminate plate and indeterminate scavenging gastropods. Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 10 mm.

c. NMING:F35216-UU SFB001
Bothriolepis dairbhrensis sp. nov. Proximal segment of the pectoral fin, with AVL and articular condyle. [ORG] corresponds to plates in original position; [RELOC] corresponds to plates relocated in life position. Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 10 mm.

d. NHM P 59677 (complete, ORG end RELOC files)
Bothriolepis dairbhrensis sp. nov. Incomplete head (and endocranial processes), ventral body armour and proximal segment of the pectoral fin. [ORG] corresponds to plates in original position; [RELOC] corresponds to plates relocated in life position. Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 10 mm.

e. NHM P 59678
Bothriolepis dairbhrensis sp. nov. Incomplete lateral and indeterminate plates of an adult individual. The scale of the reference cube edges is 10 mm.

f. NHM P 59679
Bothriolepis dairbhrensis sp. nov. Two indeterminate fragments. The scale of the reference cube edges is 10 mm.

g. NHM P 59687
Bothriolepis dairbhrensis sp. nov. Indeterminate fragments and burrows. The scale of the reference cube edges is 10 mm.

6. taxon*character matrices with different sets of analyses (readible in MESQUITE)


**LINKS TO PREVIOUSLY MENTIONED SOLUTIONS**
MESQUITE (construction of data matrix, visualisation):
https://www.mesquiteproject.org/
https://github.com/MesquiteProject/
Maddison, W. P. and D.R. Maddison. 2021. Mesquite: a modular system for evolutionary analysis. Version 3.70 http://www.mesquiteproject.org

ZEPHYR (Mesquite package for interacting with external phylogeny inference programs)
http://zephyr.mesquiteproject.org/
Maddison, D.R., & W.P. Maddison. 2021. Zephyr: a Mesquite package for interacting with external phylogeny inference programs. Version 3.20. http://zephyr.mesquiteproject.org

TNT (phylogenetic analysis)
https://onlinelibrary.wiley.com/doi/10.1111/j.1096-0031.2008.00217.x
Goloboff, P.A., Farris, J.S. and Nixon, K.C. (2008), TNT, a free program for phylogenetic analysis. Cladistics, 24: 774-786. https://doi.org/10.1111/j.1096-0031.2008.00217.x

MATERIALISE MIMICS and 3-MATIC (segmentation, 3D modelling):
https://www.materialise.com/en/healthcare/mimics-innovation-suite

DRISHTI (3D visualisation):
https://github.com/nci/drishti
Ajay Limaye; Drishti: a volume exploration and presentation tool. Proc. SPIE 8506, Developments in X-Ray Tomography VIII, 85060X (October 17, 2012)

Datasetet hänger samman med en studie av fossilt fiskmaterial från sydvästra Irland (Placodermi, Antiarchi; Givetian på Iveragh-halvön). Data består av SEM-elementkartläggning (avsnitt 1), datortomografiska bildstaplar och efterföljande arbetsfiler (dvs. segmentering, visualiseringsfiler, STL-filer och 3D PDF-filer; avsnitt 2-5), samt fylogenetiska analyser relaterade till släktet Bothriolepis som studerats i artikeln (avsnitt 6).
* Zoobank LSID för artikeln: urn:lsid:zoobank.org:pub:0438B3D4-AEAA-4000-A1CB-B5DA0ECA466F
* Zoobank LSID för taxon Bothriolepis dairbhrensis: urn:lsid:zoobank.org:act:B577F075-1EF6-48A5-8C7C-E64E36E2BC4E

Data som motsvarar artikeln

Dupret, Byrne, Castro, Hammer, Higgs, Long, Niedźwiedzki, Qvarnström, Stössel & Ahlberg. In Press. The Bothriolepis (Placodermi, Antiarcha) material from the Valentia Slate Formation of the Iveragh Peninsula (middle Givetian, Ireland): morphology, evolutionary and systematic considerations, phylogenetic and palaeogeographic implications. PLOS ONE.
med LSID urn:lsid:zoobank.org:pub:0438B3D4-AEAA-4000-A1CB-B5DA0ECA466F
och arten Bothriolepis dairbhrensis Dupret, Byrne, Castro, Hammer, Higgs, Long, Gzegorz Niedźwiedzki, Qvarnström, Stössel & Ahlberg
med LSID urn:lsid:zoobank.org:act:B577F075-1EF6-48A5-8C7C-E64E36E2BC4E

består av följande filer:

1. Elementaranalys (SEM)
utrustning: Hitachi S–3600N svepelektronmikroskop (SEM); JPG-filerna är originalutdata.

2. Dataset från datortomografi
I London kördes datortomografi på materialet med ett Nikon HMX ST 225-system (Nikon Metrology, Leuven, Belgien), utrustat med ett reflektionsmål av volfram. Detaljerade inställningsfiler justerades för varje exemplar och finns angivna i den tillhörande dokumentationsfilen "S2 Table-scan properties.xlsx". Två exemplar krävde sammanfogning med hjälp av ett särskilt framtaget NHM-skript skrivet i Octave. I Oslo utfördes skanningen med ett Nikon Metrology XT H 225 ST mikrofokus CT-instrument vid Naturhistorisk museum, Universitetet i Oslo, med 160-220 kV, 1 s exponeringstid, 3016 projektioner och med tennfilter av varierande tjocklek. Voxelupplösningen var 75 µm eller bättre. Detaljerade inställningar finns även här angivna i den tillhörande dokumentationsfilen "S2 Table-scan properties.xlsx".

3. Materialise Mimics och Drishti-filer (segmentering)

4. STL-filer

5. 3D PDF-filer
I Mimics användes varje enskild struktur som motsvarar en mask för att generera ett högkvalitativt 3D-objekt, som i sig omvandlades till en STL-fil. Varje 3D-objekt duplicerades och positionerades om i 3D, och STL-filer genererades åter. STL-filerna importerades sedan till Materialise 3-matic (v. 15.0) och omorganiserades till anatomiska ensembler (huvud, fena, etc.) i både ursprungliga och korrekta positioner. Varje STL-yta förenklades sedan och korrigerades med hjälp av följande funktioner: "Filter Sharp Triangles" med filter distance 0,01; "Filter Small Edges" med filter distance 0,01; "Improve Mesh" med shape quality high/medium, maximum geometrical error 0,07 och maximal edge length 20,0. En 3D PDF-fil genererades till slut och öppnades i Adobe Acrobat för att ta bilder som används i figurer i den relaterade artikeln.

för följande exemplar
a. NMING:F35203-UU210ab_HQ
Bothriolepis dairbhrensis sp. nov. Ofullständig lateralplatta och fragment av obestämd platta. Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic. Referenskubens kanter är 10 mm.
Notera att i Mimics-projektfilerna för detta exemplar är µm av misstag angivet som måttreferens när det skall vara mm (millimeter). All annan bearbetning har skett med förutsättningarna att måttreferensen är i millimeter.

b. NMING:F35229-CH003
Bothriolepis dairbhrensis sp. nov. Sammansättning av obestämd platta och obestämda asätande gastropoder. Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic. Referenskubens kanter är 10 mm.

c. NMING:F35216-UU SFB001
Bothriolepis dairbhrensis sp. nov. Proximalt segment av bröstfenan, med AVL och ledkondyl. [ORG] motsvarar plattor i ursprunglig position; [RELOC] motsvarar plattor som flyttats till livsläge. Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic. Referenskubens kanter är 10 mm.

d. NHM P 59677 (komplett, ORG-slut RELOC-filer)
Bothriolepis dairbhrensis sp. nov. Ofullständigt huvud (och endokraniella processer), ventralt kroppspansar och proximalt segment av bröstfenan. [ORG] motsvarar plattor i ursprunglig position; [RELOC] motsvarar plattor som flyttats till livsläge. Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic. Referenskubens kanter är 10 mm.

e. NHM P 59678
Bothriolepis dairbhrensis sp. nov. Ofullständiga laterala och obestämda plattor av en vuxen individ. Referenskubens kanter är 10 mm.

f. NHM P 59679
Bothriolepis dairbhrensis sp. nov. Två obestämda fragment. Referenskubens kanter är 10 mm.

g. NHM P 59687
Bothriolepis dairbhrensis sp. nov. Obestämda fragment och hålor. Referenskubens kanter är 10 mm.


6. taxon*karaktär-matriser med olika uppsättningar av analyser (läsbara i MESQUITE)


**LÄNKAR TILL ANVÄNDA VERKTYG**
MESQUITE (konstruktion av datamatris, visualisering)
https://www.mesquiteproject.org/
https://github.com/MesquiteProject/
Maddison, W. P. and D.R. Maddison. 2021. Mesquite: a modular system for evolutionary analysis. Version 3.70 http://www.mesquiteproject.org

ZEPHYR (Mesquite-paket för interaktion med externa fylogeni-inferensprogram)
http://zephyr.mesquiteproject.org/
Maddison, D.R., & W.P. Maddison. 2021. Zephyr: a Mesquite package for interacting with external phylogeny inference programs. Version 3.20. http://zephyr.mesquiteproject.org

TNT (fylogenetisk analys)
https://onlinelibrary.wiley.com/doi/10.1111/j.1096-0031.2008.00217.x
Goloboff, P.A., Farris, J.S. and Nixon, K.C. (2008), TNT, a free program for phylogenetic analysis. Cladistics, 24: 774-786. https://doi.org/10.1111/j.1096-0031.2008.00217.x

MATERIALISE MIMICS and 3-MATIC (segmentering, 3D-modellering):
https://www.materialise.com/en/healthcare/mimics-innovation-suite

DRISHTI (3D-visualisering):
https://github.com/nci/drishti
Ajay Limaye; Drishti: a volume exploration and presentation tool. Proc. SPIE 8506, Developments in X-Ray Tomography VIII, 85060X (October 17, 2012)
Bothriolepis (Placodermi, Arthrodira) från Iveragh-halvön (Irland) - CT-data, 3D-modeller, och fylogenetiska filer
Keywords: phylogeny; fylogeni; palaeogeography; paleogeografi; Devonian; devon; stratigraphy; stratigrafi; systematics; systematik (biologi); valentia island; valentia island; placoderm; placoderm; Bothriolepis; Bothriolepis; antiarchi; armpansarhajar; givetian; givetian; Bothriolepis dairbhrensis; Geology; Geologi; Zoology; Zoologi; Archaeology; Arkeologi; Other Natural Sciences; Annan naturvetenskap; Artefact; Artefact